Gestión administrativa y desempeño laboral de los colaboradores de la Comercializadorasan Juan SAC, año 2022 - Rios Torres, Paulo Junior (2024)
The objective of this work is to establish the relationship between administrative management and work performance of the collaborators of Comercializadora San Juan SAC, 2022. It was a non-experimental research design, with a quantitative, cross-sectional, and descriptive level approach. The population was considered to be 92 employees of Comercializadora San Juan SAC, 2022, to whom a questionnaire was applied through the survey technique. Concluding that there is a high positive relationship between administrative management and work performance of the collaborators of Comercializadora San Juan SAC, 2022.